2023
DOI: 10.3389/fmicb.2023.1136413
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors and gut microbiota: Toward better conservation of deer species

Abstract: Thousands of microbial species inhabiting the animal gut, collectively known as the gut microbiota, play many specific roles related to host nutrient metabolism and absorption, immune regulation, and protection from pathogenic bacteria. Gut microbiota composition is affected by several internal and external factors, such as the host genotype, dietary intake, breeding environment, and antibiotic exposure. As deer species are important members for maintaining ecosystem balance, understanding the effects of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It is well-established that antibiotics greatly impact the structural composition of the gut microbiota (Wang et al 2023 ). For example, an 8-week amoxicillin treatment led to diminished levels of Faecalibaterium (Pallav et al 2014 ), as did the administration of ciprofloxacin (Stewardson et al 2015 ).…”
Section: Faecalibacterium As a Therapeutic Toolmentioning
confidence: 99%
“…It is well-established that antibiotics greatly impact the structural composition of the gut microbiota (Wang et al 2023 ). For example, an 8-week amoxicillin treatment led to diminished levels of Faecalibaterium (Pallav et al 2014 ), as did the administration of ciprofloxacin (Stewardson et al 2015 ).…”
Section: Faecalibacterium As a Therapeutic Toolmentioning
confidence: 99%
“…1h-j). The results of these investigations demonstrated that, while there is a robust variation of the intestinal microbiota structure among patients subsets [25][26][27] , UC patients were characterized by a slight expansion of Proteobacteria and Actinobacteria phyla, with a decrease in Tenericutes and Verrucomicrobia (Fig. 1h).…”
Section: Introductionmentioning
confidence: 90%
“…Conversely, its deregulation has been linked to pathological processes affecting several organs and apparatuses [ 91 ]. The GM composition is the result of an intense interplay between genetic and environmental factors, such as age, sex, perinatal feeding, dietary habits, lifestyle and antibiotic exposure [ 92 ].…”
Section: Gut Microbiota Gender and Vaccinesmentioning
confidence: 99%